1. The problem statement, all variables and given/known data Given the function f(x) = (abs(x))*x +6, find f^-1(x) 2. Relevant equations 3. The attempt at a solution for x≥ 0, f(x) = x^2 + 6 y=x^2 +6 x = √(y-6) for y≥6 → f^-1(x) = √(x-6) for x≥6 for x< 0, f(x) = -x^2 + 6 y= -x^2 +6 x = √(6-y) for y<6 → f^-1(x) = √(6-x) for x<6 But the correct answer is f^-1(x) = ±√(x-6) with the domain and range as all real numbers. How do I get the inverse function to not be piecewise? Sorry about the lack of proper equations, I don't know how to use latex.